Flexural Properties of Glass and Graphite Particles Filled Polymer Composites - Ibrahim, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The effects of reinforcing polymers with glass and graphite particles on enhancing their flexural properties are investigated.   Five composites were fabricated using the same polymer matrix material with different volume fractions of reinforcement particles. They comprise glass particles and graphite particles each  having volume fractions of 20% and 30% as well as a hybrid composite having 10% glass and 10% graphite. Three-point bending tests using a Universal Testing Machine were carried out on specimens of the above mentioned composites, as well as specimens of the polymer matrix material to determine their flexural properties. The experimental test results indicate that the flexural stiffness of all the composites were markedly higher than that of the matrix material.   As for the flexural strength, composites with 20% glass, 30% graphite and the hybrid composite maintained higher flexural strength than the matrix material.